Jamaica : Financial System Stability Assessment. (IMF Staff Country Reports; Country Report ;, 2018)
The macroeconomic environment has improved, reflecting the authorities' efforts, supported by an IMF arrangement. Previously, years of high fiscal deficits, public enterprise borrowing, and financial sector bailouts led to rapid government debt accumulation, crowded out private credit, increased financial dollarization, and stifled economic growth. Fiscal discipline has been essential to reduce public debt (to about 100 percent of GDP). With government debt accounting for a sizable share of financial institutions' assets, falling interest rates on government debt are leading to a search for yield. Also, entrenched structural obstacles, including high crime, bureaucratic processes, insufficient labor force skills, and poor access to finance still constrain economic growth. The authorities have made good progress in implementing the 2006 FSAP recommendations. Work on the regulatory framework has significantly advanced in several areas such as securities dealers' activities, powers to the Bank of Jamaica (BoJ), payment systems, and the introduction of the centralized securities depository. However, the crisis management framework and risk-based supervision work has been lagging.